Social Aspects of Livestock Waste Management in Cyprus - Longo, Stefano; Malamis, Simos; Katsou, Evina; Costa, Costas; Theologidis, Christodoulos; Fatone, Francesco (My University, 2016)
This work examined the social perception of the population towards the management of livestock waste (LWM) in Cyprus. A questionnaire was designed based on major concerns of citizen extracted from literature reviews. These concerns were integrated into questions related to impact aspect of LWM, people perception on the subject, and to the management aspect. The questionnaire was sent to more than 100 individuals residing close to LWM facilities. A relation between risk perception and level of information was found. On a scale 1–5, the responses showed that the greatest problems as perceived by the population are odour issues (3.9), health issues and the adverse impact on property values (both 3.2). Although 81 % of the respondents stated that they have some information or are well informed about LWM in their area, they often tend to evaluate improperly functionality of the facility. Odour emissions are seen as an indication of improper operation of the facility; respondents usually agree on the fact that the current livestock waste treatment system is not adequate compared to the requirements. Finally, the participants in the survey believe that LWM activities cannot significantly improve the employment level in Cyprus. The job estimate for biogas power plant is 0.62 job-years/GWh, which is higher compared to other type of renewable energy installations.
Keywords: Indicators; Job creation; Livestock waste management; Questionnaire survey; Social impact assessment; Green--Πράσινο; Αειφόρες Πόλεις και Κοινωνία--Sustainable Cities and Communities; Καθαρό Νερό και υγιεινή--Clean Water and Sanitation (Διαχείριση νερού και αποβλήτων)